2019
DOI: 10.1073/pnas.1817183116
|View full text |Cite
|
Sign up to set email alerts
|

Loss of postnatal quiescence of neural stem cells through mTOR activation upon genetic removal of cysteine string protein-α

Abstract: Neural stem cells continuously generate newborn neurons that integrate into and modify neural circuitry in the adult hippocampus. The molecular mechanisms that regulate or perturb neural stem cell proliferation and differentiation, however, remain poorly understood. Here, we have found that mouse hippocampal radial glia-like (RGL) neural stem cells express the synaptic cochaperone cysteine string protein-α (CSP-α). Remarkably, in CSP-α knockout mice, RGL stem cells lose quiescence postnatally and enter into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 58 publications
(84 reference statements)
1
30
0
Order By: Relevance
“…At the same time, a persistent hyper-proliferation induced by mTOR hyper-activation may lead to the exhaustion of the NSCs pool. Such an effect can be reverted by the administration of the gold-standard mTOR inhibitor rapamycin [104]. Remarkably, the hyper-activation of mTOR signaling in transgenic mice results in a marked expansion of the SVZ stem cell compartment and subsequent glioma development [105].…”
Section: Mtor Function In Glioblastoma Cancer Stem Cellsmentioning
confidence: 99%
“…At the same time, a persistent hyper-proliferation induced by mTOR hyper-activation may lead to the exhaustion of the NSCs pool. Such an effect can be reverted by the administration of the gold-standard mTOR inhibitor rapamycin [104]. Remarkably, the hyper-activation of mTOR signaling in transgenic mice results in a marked expansion of the SVZ stem cell compartment and subsequent glioma development [105].…”
Section: Mtor Function In Glioblastoma Cancer Stem Cellsmentioning
confidence: 99%
“…In a recent study by Nieto-González et al, CSPα function has been linked to the mTOR signaling pathway. In this study, the authors found a hyperactivation of the mTOR pathway causing hyperproliferation of neurospheres generated from CSPa-deficient mice, although the precise mechanism by which this occurs is not yet resolved [185]. mTOR signaling is highly connected to lysosomal metabolism being influenced by lysosomal signals and negatively regulating autophagy [107,109].…”
Section: Cln8-while Cln6 Localizes Specifically To the Er Cln8 Cyclementioning
confidence: 84%
“…A focal point of metabolic signaling is the nutrientsensitive protein complex mTORC1, which balances protein biosynthesis and autophagy to meet anabolic demands 33 . Regulation of mTORC1 34 is essential to prevent stem cell over-activation 35 and maintain quiescence 36 and loss of mTORC1 inhibition results in depletion of hematopoietic stem cells 37 . Sestrins are a unique class of metabolic regulators that titrate mTORC1 signaling and act as oxidative stress sensors, but their roles in adult stem cells has yet to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating our data suggest Sestrins are important regulators of MuSC metabolism and the quiescent state. Several studies have shown that hyperactivation of mTORC1 results in stem cell loss 34,36 and interruptions to the maintenance of quiescence but none have yet demonstrated this behavior through Sestrins. Accordingly, Sestrin-dependent changes may be strong targets for…”
Section: Discussionmentioning
confidence: 99%